EFFECTS OF RISPERIDONE ON LEARNING AND MEMORY PARAMETERS IN EXPERIMENTAL MODEL OF AUTISM - M. Varadinova; G. Bogdanov; P. Markova (Trakia Journal of Sciences)
Risperidone is the most widely used drug for treatment of irritability and aggression of children with autism. However, its effects on some cognitive parameters are not well understood. The present study was undertaken to assess the effects of risperidone on learning and memory parameters in shuttle-box test of rats in experimental model of autism. Our results demonstrated that administration of risperidone had beneficial effects on learning and memory of rats with experimental autism. Our data suggest the potential role of risperidone in modulating brain development, behavior and cognition in individuals with autistic features.